2009
DOI: 10.1029/2008je003133
|View full text |Cite
|
Sign up to set email alerts
|

Near‐IR oxygen nightglow observed by VIRTIS in the Venus upper atmosphere

Abstract: [1] We present observations of both the (0-0) and (0-1) bands at 1.27 and 1.58 mm of the O 2 (a 1 D g À X 3 S g À ) nightglow made with the Visible and Infrared Thermal Imaging Spectrometer (VIRTIS) instrument aboard Venus Express. The observations were conducted in both nadir and limb viewing modes, the latter constituting the first systematic investigation into the vertical distribution of the volume emission rate of the infrared oxygen nightglow in Venus' upper atmosphere. Limb measurements from 42 orbits c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
98
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 55 publications
15
98
0
Order By: Relevance
“…They found that the peak altitude of the O 2 ð 1 D g Þ volume emission rate is typically located between 95 and 100 km, with a mean value of 97:4 72:5 km. A similar conclusion was reached by Piccioni et al (2009). Observations by VIRTIS in the nadir mode have been used to construct statistical maps of the Venus atmosphere in the O 2 emission band (Gé rard et al, 2008b;Piccioni et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…They found that the peak altitude of the O 2 ð 1 D g Þ volume emission rate is typically located between 95 and 100 km, with a mean value of 97:4 72:5 km. A similar conclusion was reached by Piccioni et al (2009). Observations by VIRTIS in the nadir mode have been used to construct statistical maps of the Venus atmosphere in the O 2 emission band (Gé rard et al, 2008b;Piccioni et al, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…A similar conclusion was reached by Piccioni et al (2009). Observations by VIRTIS in the nadir mode have been used to construct statistical maps of the Venus atmosphere in the O 2 emission band (Gé rard et al, 2008b;Piccioni et al, 2009). These maps indicate the region of enhanced emission is centered on the antisolar point.…”
Section: Introductionmentioning
confidence: 74%
“…It is well adapted to the observation of the O 2 ða 1 DÞ 1.27 lm nightglow in both nadir and limb modes. The horizontal distribution of the emission brightness was studied from nadir VIRTIS observations by Gérard et al (2008b), Piccioni et al (2009) and Soret et al (2012). They found the highest intensity near the antisolar point, with maximum values of respectively 3 MR, 1.2 MR and 1.6 MR (MegaRayleigh) and a mean intensity for the nightside of 1.3 MR, 0.52 MR and 0.50 MR, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Crisp et al, 1996;Hueso et al, 2008;Krasnopolsky, 2010;Ohtsuki et al, 2005Ohtsuki et al, , 2008Bailey et al, 2008) and space-borne observations from Venus Express have been conducted. The Visible and Infrared Thermal Imaging Spectrometer (VIRTIS) instrument (Drossart et al, 2007;Piccioni et al, 2009) is composed of two spectrometers, including the VIRTIS-M-IR instrument. It is well adapted to the observation of the O 2 ða 1 DÞ 1.27 lm nightglow in both nadir and limb modes.…”
Section: Introductionmentioning
confidence: 99%
“…VIRTIS-M-IR covers the infrared spectral range from 1 to 5 µm and can observe both in nadir and limb viewing geometries (Drossart et al, 2007;Piccioni et al, 2009). Observations with VIRTIS-M were made between 14 April 2006 (orbit VI0023_01) and 14 October 2008 (orbit VI0907_05).…”
Section: Virtis Observationsmentioning
confidence: 99%